2015
DOI: 10.1089/cyber.2014.0371
|View full text |Cite
|
Sign up to set email alerts
|

Cyberbullying, Depression, and Problem Alcohol Use in Female College Students: A Multisite Study

Abstract: Cyberbullying and its effects have been studied largely in middle and high school students, but less is known about cyberbullying in college students. This cross-sectional study investigated the relationship between involvement in cyberbullying and depression or problem alcohol use among college females. Two hundred and sixty-five female students from four colleges completed online surveys assessing involvement in cyberbullying behaviors. Participants also completed the Patient Health Questionnaire-9 (PHQ-9) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
126
3
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(139 citation statements)
references
References 51 publications
6
126
3
4
Order By: Relevance
“…6,10,25,29 They are also in agreement with previous studies that report positive associations between CV and alcohol and drug use. 25,29 The absence of an association between CV and self-reported general health in the current study suggests that the association with CV may be specific to mental health and substance use. Findings from the current study suggest that adolescence may be a particularly vulnerable developmental period for exposure to CV and its adverse consequences on mental health and substance use.…”
Section: Cyberbullying and Health Outcomessupporting
confidence: 92%
“…6,10,25,29 They are also in agreement with previous studies that report positive associations between CV and alcohol and drug use. 25,29 The absence of an association between CV and self-reported general health in the current study suggests that the association with CV may be specific to mental health and substance use. Findings from the current study suggest that adolescence may be a particularly vulnerable developmental period for exposure to CV and its adverse consequences on mental health and substance use.…”
Section: Cyberbullying and Health Outcomessupporting
confidence: 92%
“…Tendencies of more depressive symptoms among cyberbully-victims than cyberbullies and cybervictims were not statistically significant. Several studies indicate most depression among cyberbully-victims (Brunstein Klomek et al, 2007;Dupper, 2013;Kowalski & Limber, 2013;Selkie et al, 2015), but this was not supported in our study. Hinduja and Patchin (2010) found that adolescents involved in cyberbullying struggle more than non-involved adolescents when it comes to suicidal ideation, which is related to depression.…”
Section: Depression Anxiety and Self-harmcontrasting
confidence: 99%
“…Previous studies have reported on higher levels of depressive symptoms, anxiety, low self-esteem, somatization and hostility in both cybervictims and cyberbullies (Kokkinos et al, 2014;Nixon, 2014;Tural Hesapcioglu & Ercan, 2017). However, adolescents who have been shown to have the highest risk of developing mental health problems such as anxiety and depression are those who are both cyberbullies and victims (cyberbully-victims) (Brunstein Klomek et al, 2007;Dupper, 2013;Espelage & Holt, 2013;Selkie et al, 2015). We thus expect to find the same in our study, and hypothesize that those who report both to be cyberbullies and victims will report the highest level of adverse mental health outcomes.…”
Section: Mental Health Problemsmentioning
confidence: 99%
“…Fear, especially, was a common emotion experienced by victims, and was further augmented when victims did not know their attackers. Selkie et al, (2015) reported among 265 female college students, being engaged in cyberbullying as bullies, victims, or both led to higher rates of depression and alcohol use. Similarly, Sourander et al (2010) reported that being cyber-victimized was associated with conduct and emotional problems, not feeling safe at school, physical pain, frequent smoking, and misuse of alcohol.…”
Section: Consequences Of Cyberbullyingmentioning
confidence: 98%
“…Research has indicated that when individuals in high school have been cyber bullies or cyber victims, they tend to fall into these same categories in post-secondary schools (Selkie, Kota, Chan, & Moreno, 2015;Kraft & Wang, 2010;Slonje & Smith, 2008). Furthermore, the methods by which individuals were cyberbullied or cyberbullied others (e.g.…”
Section: The Link Between Traditional and Cyber Bullyingmentioning
confidence: 99%